Primary CNS lymphoma initially diagnosed as vasculitis. Issue 1 (February 2020) - Feldman, Lauren; Li, Yuebing; Ontaneda, Daniel
Abstract : Purpose of review: A vasculitic pattern of injury seen on brain biopsy can be attributed to a multitude of primary or secondary disorders, leading to diagnostic challenges for clinicians. Recent findings: This report describes the clinical presentation and histopathologic findings in 2 patients who initially received a diagnosis of primary CNS vasculitis, but did not show long-term response to treatment. In both cases, a second biopsy was performed, and the final diagnosis was primary CNS lymphoma (PCNSL). Summary: Analyzing diagnostically challenging cases can increase recognition of PCNSL and improve outcomes in this rare condition.